CORRELATION OF SERUM ZINC LEVELS WITH SEVERITY AND DISEASE ACTIVITY IN VITILIGO PATIENTS AT SANJIWANI GIANYAR HOSPITAL - Sayu Widiawati; Made Budiani; Pradnya Iswara (JURNAL WIDYA MEDIKA, 2023)
Vitiligo is autoimmune disease, characterized by well defined milky-white macule, caused by destruction of melanocyte selectively. Management of vitiligo is still challenging due to the pathogenesis is not yet fully understood, and vitiligo can caused significant psychological distress to the patients. Several studies reveal the role of zinc as an important element in the prevention and treatment of vitiligo based on zinc's function as an antiapoptotic, as a bull against free radicals, and as an important element in melanogenesis by stimulating cell mediated immunity activity, zinc and alpha melanocyte stimulating hormone. We conducted an analytical cross-sectional study that aims to determine the correlation between plasma zinc levels and the severity of vitiligo using the VASI score and vitiligo disease activity calculated based on the VIDA score. The results showed that there was a strong negative correlation between serum zinc levels and the VASI score, with a correlation coefficient or r = -0.668 and p